Constructing Model To Discover The Effect Of Religiosity And Spirituality On Organizational Performance - Hatem Mohammed Rouhoma; Bablu Kumar Dhar; Mohamed Muftah Osman; Kalsom Ali (Forecast Publisher, 2024)
The purpose of this paper is to develop a model to explore the impact of religiosity and spirituality on performance organizations through organizational commitment. This study adopted Religiosity and Spirituality as independent variables, organizational commitment as mediating and Performance as a dependent variable. The study is based on conceptual research. Through this study, a model will be proposed to find out the relationship among religiosity, spirituality, organizational commitment and organizational performance. Based on the developed model, the study will continue to find out the impact of radiosity and spirituality through organizational commitment on performance of different types of business. Applying this empirical study, organizations may generate new policies and strategies for improving performance in multicultural and multi-religious organizations.